Genomic analysis of Salmonella isolated from surface water and animal sources in Chile reveals new T6SS effector protein candidates - Amaya, Fernando A.; Blondel, Carlos J.; Reyes-Méndez, Felipe; Rivera, Dácil; Moreno-Switt, Andrea; Toro, Magaly; Badilla, Consuelo; Santiviago, Carlos A.; Pezoa, David (Frontiers in Microbiology, 2024)
Type VI Secretion Systems (T6SS), widely distributed in Gram-negative bacteria, contribute to interbacterial competition and pathogenesis through the translocation of effector proteins to target cells. Salmonella harbor 5 pathogenicity islands encoding T6SS (SPI-6, SPI-19, SPI-20, SPI-21 and SPI-22), in which a limited number of effector proteins have been identified. Previous analyses by our group focused on the identification of candidate T6SS effectors and cognate immunity proteins in Salmonella genomes deposited in public databases. In this study, the analysis was centered on Salmonella isolates obtained from environmental sources in Chile. To this end, bioinformatics and comparative genomics analyses were performed using 695 genomes of Salmonella isolates representing 44 serotypes obtained from surface water and animal sources in Chile to identify new T6SS effector proteins. First, T6SS gene clusters were identified using the SecreT6 server. This analysis revealed that most isolates carry the SPI-6 T6SS gene cluster, whereas the SPI-19 and SPI-21 T6SS gene clusters were detected in isolates from a limited number of serotypes. In contrast, the SPI-20 and SPI-22 T6SS gene clusters were not detected. Subsequently, each ORF in the T6SS gene clusters identified was analyzed using bioinformatics tools for effector prediction, identification of immunity proteins and functional biochemical prediction. This analysis detected 20 of the 37 T6SS effector proteins previously reported in Salmonella. In addition, 4 new effector proteins with potential antibacterial activity were identified in SPI-6: 2 Rhs effectors with potential DNase activity (PAAR-RhsA-NucA_B and PAAR-RhsA-GH-E) and 2 effectors with potential RNase activity (PAAR-RhsA-CdiA and RhsA-CdiA). Interestingly, the repertoire of SPI-6 T6SS effectors varies among isolates of the same serotype. In SPI-19, no new effector protein was detected. Of note, some Rhs effectors of SPI-19 and SPI-6 present C-terminal ends with unknown function. The presence of cognate immunity proteins carrying domains present in bona fide immunity proteins suggests that these effectors have antibacterial activity. Finally, two new effectors were identified in SPI-21: one with potential peptidoglycan hydrolase activity and another with potential membrane pore-forming activity. Altogether, our work broadens the repertoire of Salmonella T6SS effector proteins and provides evidence that SPI-6, SPI-19 and SPI-21 T6SS gene clusters harbor a vast array of antibacterial effectors.